(3QSGdI aj GdefWbs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; GYde Cf fSHI GdHUjQI Edi eOQcGJgG cfSHI GdHUQ Edi eMShSGJgG (B( (3cPG (B) (3hCfJ EPG fXQJ aj GdeQBI hTGgOJ UhQI ajgG adc gfGc MGdJGf (B: (3GdChdi Cf jchf eJhLgG Edi Jdc GdUhQI eTGgOG EjGgG bUOGs
(3BNQgG (B:s
(3bGe CHh RjO hChbYJ GdfSHI HjfgeG de jQJHW HZjQg CUdG hdh cGf eYfi bGe CHhg CjVG Pdc de jQJHW HRjO hde jbY (B( ) (3hef KeI JSeY GdfMGI jbhdhf (B: (3bGe CHhg LedI hdjS HcdGe dJLQjOg Yf EjbGY GdfSHI Hjf WQajgG dbQjfIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdadSaI hGdefWbs